2016
DOI: 10.1016/j.jvs.2016.05.078
|View full text |Cite
|
Sign up to set email alerts
|

Treatment indications for and outcome of endovascular repair of type B intramural aortic hematoma

Abstract: BMT is justified in uncomplicated IMHB. However, IMHB becomes complicated in the majority of patients within 20 days. TEVAR in complicated IMHB is feasible but associated with a substantial aortic reintervention rate, reflecting technical challenges and fragile aortic wall conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 36 publications
1
38
0
1
Order By: Relevance
“…In our study, the occurrence of FIDs was greater than that reported by Moral et al (37% vs 10%, Table ) . The rates of disease progression and mortality were lower in the FID group (63% vs 91%; 25% vs 36%, Table ) and clearly higher than those reported by Bischoff et al (0% mortality) in the no‐FID group . One potential explanation for the high occurrence of FIDs and poor clinical outcome in the no‐FID group in this retrospective study is the inclusion of more severe and less stable cases (Table ), including patients with a maximum aorta diameter ≥ 45 mm 2 and a hematoma thickness ≥ 10 mm.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In our study, the occurrence of FIDs was greater than that reported by Moral et al (37% vs 10%, Table ) . The rates of disease progression and mortality were lower in the FID group (63% vs 91%; 25% vs 36%, Table ) and clearly higher than those reported by Bischoff et al (0% mortality) in the no‐FID group . One potential explanation for the high occurrence of FIDs and poor clinical outcome in the no‐FID group in this retrospective study is the inclusion of more severe and less stable cases (Table ), including patients with a maximum aorta diameter ≥ 45 mm 2 and a hematoma thickness ≥ 10 mm.…”
Section: Discussionmentioning
confidence: 89%
“…One potential explanation for the high occurrence of FIDs and poor clinical outcome in the no‐FID group in this retrospective study is the inclusion of more severe and less stable cases (Table ), including patients with a maximum aorta diameter ≥ 45 mm 2 and a hematoma thickness ≥ 10 mm. 3 Moreover, Bischoff et al also reported similar geometrical changes and worse clinical outcomes in unstable cases. Furthermore, Ye et al suggested that these unstable patients should be classified as “complicated” and treated with prophylactic TEVAR to prevent progression of the hematoma .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Advocators of the necessary TEVAR procedure for IMHB patients with disease progression and uncontrollable syndromes have reported that it could prevent further progression of IMHB and achieve a better prognosis than medical treatment alone . However, for patients with disease progression and uncontrollable syndromes who lack sufficient medical treatment, the fragile aortic wall will probably result in higher postoperative mortality, which is the major problem with the “watchful waiting strategy.” Therefore, other physicians have advocated a more aggressive treatment (prophylactic TEVAR during the acute phase) for IMHB patients with disease progression when the syndromes were still controllable, and better outcomes than those with the conventional “watchful waiting strategy” have been reported . Moreover, many factors can predict the disease progression and outcome of IMHB patients, such as maximum aortic diameter (≥45 mm), increased pleural effusion, hematoma thickness (≥10 mm), focal intimal disruption (FID) development and an elevated C‐reactive protein (CRP) level (≥7.2 mg/dL) .…”
Section: Introductionmentioning
confidence: 99%